Bootstrap pointwise confidence intervals for covariate-adjusted survivor functions in the Cox model. (March 2019) - Ruhe, Constantin
Survival functions are a common visualization of predictions from the Cox model. However, neither Stata'sstcurve command nor the communitycontributedscurve tvc command allows one to estimate confidence intervals. In this article, I discuss how bootstrap confidence intervals can be formed for covariate-adjusted survival functions in the Cox model. The newbsurvci command automates this procedure and allows users to visualize the results.bsurvci enables one to estimate uncertainty around survival functions estimated from Cox models with time-varying coefficients, a capability that was not previously available in Stata. Furthermore, it provides Stata users with an additional option for survival estimates from Cox models with proportional hazards by allowing them to choose between bootstrap confidence intervals usingbsurvci and asymptotic confidence intervals from an existing community-contributed command, survci . Because asymptotic confidence intervals make distributional assumptions when constructing confidence intervals, the bootstrap procedure proposed in this article provides a nonparametric alternative.